Dynamic Fascial Closure With Vacuum-Assisted Wound Closure and Mesh-Mediated Fascial Traction (VAWCM) Treatment of the Open Abdomen—An Updated Systematic Review - Petersson, Patrik; Petersson, Ulf (Frontiers in Surgery, 2020)
Introduction: Several different temporary abdominal closure techniques are described in the context of open abdomen treatment. Techniques based on dynamic fascial closure combined with negative pressure therapy have gained popularity and seem to result in the highest fascial closure rates without increased complications and is highlighted in recent guidelines and recommendations. One dynamic closure technique is the vacuum assisted wound closure and mesh-mediated fascial traction (VAWCM) technique, first described in 2007. The aim of this systematic review was to evaluate the VAWCM-technique regarding a number of short- and long-term results. Materials and methods: A systematic literature search was performed in PubMed, EMBASE and Cochrane Library databases for articles published between January 1, 2006 and May 8, 2020. The review was independently performed by the two authors according to the PRISMA statements for reporting systematic reviews and meta-analyses. Results were pooled for presentation of weighted means when applicable. Results: 220 articles were screened by title and abstract. 32 articles were assessed for eligibility by full-text review and 15 articles finally remained for review. A total of 600 patients treated with VAWCM were included. The pooled weighted means were: fascial closure 83.5%; enteroatmospheric fistula 5.6%; planned ventral hernia 6.2%; in-hospital survival 72%; and, incisional hernia incidence 40.5%. Long-term survival ranged between 22% and 72%. Quality of life (SF-36) was reported in two studies showing lower scores than the population mean especially in physical domains. Incisional hernia resulted in lower scores in one but not in the other study. Discussion: The results of 600 VAWCM treated patients from 15 studies were evaluated in this systematic review. Earlier findings with high fascial closure rates, low enteroatmospheric fistula and planned ventral hernia rates as well as high incisional hernia incidences were underlined. Permanent mesh for efficient fascial traction and reinforcement at fascial closure seem to be the next step in evolving an optimal temporary closure technique in open abdomen treatment.